Preparation, Characterization, and Biological Evaluation of a Hydrophilic Peptide Loaded on PEG-PLGA Nanoparticles - Lisa Marinelli; Michele Ciulla; Jeffrey A. S. Ritsema; Cornelus F. van Nostrum; Ivana Cacciatore; Marilisa Pia Dimmito; Ferdinando Palmerio; Giustino Orlando; Iole Robuffo; Rossella Grande; Valentina Puca; Antonio Di Stefano (MDPI AG, 2022)
The encapsulation of peptides and proteins in nanosystems has been extensively investigated for masking unfavorable biopharmaceutical properties, including short half-life and poor permeation through biological membranes. Therefore, the aim of this work was to encapsulate a small antimicrobial hydrophilic peptide (H-Ser-Pro-Trp-Thr-NH2, FS10) in PEG-PLGA (polyethylene glycol-poly lactic acid-co-glycolic acid) nanoparticles (Nps) and thereby overcome the common limitations of hydrophilic drugs, which because they facilitate water absorption suffer from rapid degradation. FS10 is structurally related to the well-known RNAIII inhibiting peptide (RIP) and inhibits S. aureus biofilm formation. Various parameters, including different method (double emulsion and nanoprecipitation), pH of the aqueous phase and polymeric composition, were investigated to load FS10 into PEG-PLGA nanoparticles. The combination of different strategies resulted in an encapsulation efficiency of around 25% for both the double emulsion and the nanoprecipitation method. It was found that the most influential parameters were the pH-which tailors the peptides charge-and the polymeric composition. FS10-PEG-PLGA nanoparticles, obtained under optimized parameters, showed size lower than 180 nm with zeta potential values ranging from −11 to −21 mV. In vitro release studies showed that the Nps had an initial burst release of 48-63%, followed by a continuous drug release up to 21 h, probably caused by the porous character of the Nps. Furthermore, transmission electron microscopy (TEM) analysis revealed particles with a spherical morphology and size of around 100 nm. Antimicrobial assay showed that the minimum inhibitory concentration (MIC) of the FS10-loaded Nps, against S. aureus strains, was lower (>128 µg/mL) than that of the free FS10 (>256 µg/mL). The main goal of this work was to develop polymeric drug delivery systems aiming at protecting the peptide from a fast degradation, thus improving its accumulation in the target site and increasing the drug-bacterial membrane interactions.